THE TAQNIN OF INDONESIAN ISLAMIC LAW DYNAMIC (State Islamic University (UIN) of Sunan Ampel Surabaya, 2015)
Taqnin with the meaning of legislation on Islamic aspects actually has been a long story in Indonesia. It can be traced in Islamic courts in the archipelago. In the colonial era, the Dutch once accommodated certain aspects of Islamic law, until they decided to limit it. It especially can be seen in the institution of religious court. After the independence, the taqnin was reintroduced. It can be seen from the Piagam Jakarta (Jakarta Charter) which included the statement of “Belief in God Almighty by following the sharia for its adherents”. However, this statement was edited to accommodate the aspiration of non-Muslims and the nationalists. In the following periods, legislation of certain aspects of Islam gained momentum in the late period of the New Order after Suharto sought political supports from Muslims. In the reformation era, the democratic atmosphere has opened a wider space for the efforts of taqnin.